Audit of the Ward Environment in an Inpatient Autism Unit - Azmathulla Khan Hameed; Jhansi Seekulo (BJPsych Open)
Aims: Creating an optimal ward environment for autistic inpatients is essential for their well-being and therapeutic progress. This audit aimed to assess the inpatient ward environment of two autism rehabilitation wards – Spring Center (a locked rehabilitation ward) and Spring Wing (an open rehabilitation ward) – against the Gold Standard Environmental Standards for Learning Disability (LD) and Autism Spectrum Disorder (ASD) inpatient hospitals, as well as the Quality Network for Learning Disability (QNLD) standards.